Performance Analysis of Submerged Vehicle Electric Propulsion with DC Motor 2x1850 kW 380 Volt which Supplied Power 10260 AH on 190 VDC in Series and Parallel Circuits - Indra Ranu Kusuma; Sardono Sarwito; Annisa Maya Shabrina (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
An electric DC motor that is used as a main propulsion, typically used on ships with high maneuverability, special ships, ships wtih great cargo load, and the ships that use prime movers non-reversible (generally using a gas turbine, steam turbine and high-speed diesel in its use is unlikely to reverse its rotation quickly). As for the expected results we will obtain the characteristics (such as torque and rotation) on a series DC motor series and in parallel on the propulsion system, determines where an efficient circuit for the propulsion system, getting long use of batteries used for such needs. In this research will be assessed numerically by simulation using MATLAB-Simulink the drive system by using a DC motor in a vehicle submerged was carried out together series and parallel. The result obtained is the same input voltage of 190 Volt same torque value of 140 Nm is generated at the motor circuit series and parallel. So that a series circuit, generating a service speed of 12 knots and 21.5 knots using a converter, and usually when submerged condition in the sea. For parallel circuit produces speed of 14 knots and 11 knots using a converter.